Desentralisasi Penyediaan Program Pendidikan Inklusif bagi Penyandang Disabilitas di Indonesia: Systematic Literature Review - Septi Wulandari; Suprapti Suprapti; Drajat Tri Kartono (Publisia: Jurnal Ilmu Administrasi Publik, 2022)
The Indonesian government implements inclusive education in order to help people with disabilities from an early age adapt to their environment. Educated adults with disabilities are expected to be able to meet their needs independently and actively participate in society. The aim of this research is to ascertain whether inclusive education can replace special schools and how well these services serve the needs of students with disabilities. This research is expected to be a tool for policy makers to evaluate existing inclusive education. This study aims to analyze whether special education at present still needs to be maintained with an increase in the implementation of inclusive education programs in Indonesia. The research method is a systematic literature review with PRISMA. The results showed that there was an unpreparedness of the government and educational institutions in accommodating the needs of children with disabilities. On the other hand, the community still needs education in accepting the presence of children with disabilities to coexist with common children. In general, special education is stillneeded as an initial facility to prepare children with disabilities before taking education in inclusive schools and centers for the development of children with disabilities. Research recommendations that can be carried out in the future are by connecting the variables of decentralization and inclusive education with other variables that are rarely studied and will produce new novelties.